Critical Factors Determining The Adoption of Sustainable Upland Agriculture In Upland Lawu, Indonesia - Karyanto, Puguh; Hanapi, Mohammad (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2023)
Several sustainable farming practices have been introduced and have shown a low farmer participation. This paper scrutinizes factors behind the poor adoption of sustainable upland agriculture by engaging the DPSIR in combination with the framework of Capacity-Incentive and Environmental Degradation. This paper employed a simple random sampling method by applying a questionnaire to 408 farmers. We used multiple linear regression analysis to know the linkage between the predictor and the dependent variable. The resulted R-Square was 0.649, with the F statistic less than 0.05. The regression model can explain the linkage between the proposed predictors and the dependent variable. Governmental incentive is the significant predictor affecting the adoption of sustainable upland agriculture. Ensuring the profitability of it by facilitating market channels, credit, and allocating subsidies for organic input are critical. Building human capital in agriculture through services is also critical in strengthening the upland farmers’ confidence to adopt sustainable agriculture.